La comunidad escolar: colectividad hacia la investigación transdisciplinar - Castañeda Lozano, Yebrail (Educación y Ciudad, 2020)
The following article has the purpose of describing the budgets that the school community requires to move from a disciplinary school of simplicity to the school of transdisciplinarity of investigative complexity. In order to develop this thesis, the developments of the transdisciplinary research attitude, the form of the emergence of knowledge and the modes of communicative proposition will be analyzed. The school community every time has to live up to a society illustrated by the media so that it can socialize and communicate its diverse research results.